The Role of SUMO1 Modification of SOX9 in Cartilage Development Stimulated by Zinc Ions in Mice - Na Xue; Jing Zhao; Jing Yin; Liang Liu; Zhong Yang; Shuchao Zhai; Xiyun Bian; Xiang Gao (Organogenesis)
Zinc ions play a pivotal role in facilitating the development of cartilage in mice. Nevertheless, the precise underlying mechanism remains elusive. Our investigation was centered on elucidating the impact of zinc deficiency on cartilage maturation by modulating SUMO1 and UBC9 at both the protein and mRNA levels. We administered a regimen inducing zinc deficiency to gravid mice from E0.5 until euthanasia. Subsequently, we subjected the embryos to scrutiny employing HE, Safranin O staining and IHC. Primary chondrocytes were isolated from fetal mouse femoral condyles and utilized for Western blot analysis to discern the expression profiles of SUMO1, SUMO2/3, UBC9, SOX9, MMP13, Collagen II, RUNX2, and aggrecan. Furthermore, ATDC5 murine chondrocytes were subjected to treatment with ZnCl2, followed by RT-PCR assessment to scrutinize the expression levels of MMP13, Collagen II, RUNX2, and aggrecan. Additionally, we conducted Co-IP assays on ZnCl2-treated ATDC5 cells to explore the interaction between SOX9 and SUMO1. Our investigation unveiled that zinc deficiency led to a reduction in cartilage development, as evidenced by the HE results in fetal murine femur. Moreover, diminished expression levels of SUMO1 and UBC9 were observed in the IHC and Western blot results. Furthermore, Western blot and Co-IP assays revealed an augmented interaction between SOX9 and SUMO1, which was potentiated by ZnCl2 treatment. Significantly, mutations at the SUMOylation site of SOX9 resulted in alterations in the expression patterns of crucial chondrogenesis factors. This research underscores how zinc ions promote cartilage development through the modification of SOX9 by SUMO1.